Bystanders’ collective responses set the norm against hate speech - Zapata, J; Sulik, J; von Wulffen, C; Deroy, O (Springer Nature, 2024)
Hate speech incidents often occur in social settings, from public transport to football stadiums. To counteract a prevailing passive attitude towards them, governmental authorities, sociologists, and philosophers stress bystanders’ responsibility to oppose or block hate speech. Here, across two online experiments with UK participants using custom visual vignettes, we provide empirical evidence that bystanders’ expression of opposition can affect how harmful these incidents are perceived, but only as part of a collective response: one expressed by a majority of bystanders present. Experiment 1 (N = 329) shows that the silence or intervention of three bystanders affects the harm caused by hate speech, but one bystander does not. Experiment 2 (N = 269) shows this is not simply a matter of numbers but rather one of norms: only unanimous opposition reduces the public perception of the damage created by the incident. Based on our results, we advance an empirical norm account: group responses to hate speech modulate its harm by indicating either a permissive or a disapproving social norm. Our account and results, showing the need to consider responses to hate speech at a collective level, have direct implications for social psychology, the philosophy of language and public policies.